2016
DOI: 10.1111/mcn.12398
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of the treatment of severe acute malnutrition in West Africa

Abstract: We present an updated cost analysis to provide new estimates of the cost of providing community-based treatment for severe acute malnutrition, including expenditure shares for major cost categories. We calculated total and per child costs from a provider perspective. We categorized costs into three main activities (outpatient treatment, inpatient treatment, and management/administration) and four cost categories within each activity (personnel; therapeutic food; medical supplies; and infrastructure and logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 10 publications
3
26
2
1
Order By: Relevance
“…For instance, a cost analysis study that compared the costs of outpatient and inpatient treatment in Ethiopia reported the mean cost per child treated to be US$284.56 in an inpatient facility and US$134.88 in an outpatient center. A similar study in West Africa reported that the outpatient and inpatient treatment costs per child were €75.50 and €134.57, respectively [11,12].…”
Section: Sample Size Determinationmentioning
confidence: 92%
“…For instance, a cost analysis study that compared the costs of outpatient and inpatient treatment in Ethiopia reported the mean cost per child treated to be US$284.56 in an inpatient facility and US$134.88 in an outpatient center. A similar study in West Africa reported that the outpatient and inpatient treatment costs per child were €75.50 and €134.57, respectively [11,12].…”
Section: Sample Size Determinationmentioning
confidence: 92%
“…A programme integrating SAM and MAM treatment in a single MUAC-based protocol using only RUTF showed the cost of RUTF for integrated treatment to be less than half that for standard SAM management (11) . Other studies found that identification and treatment of children earlier in the wasting process led to fewer hospitalisations and that inpatient care was shown to be twice as costly as outpatient SAM management (12,13) . Furthermore, the treatment of MAM has been shown to be cost-effective in reducing mortality risk by more than 10 % (14) .…”
mentioning
confidence: 99%
“…More efficient and cost‐effective ways of preventing and treating SAM would be much welcomed by stakeholders at national and global levels, given the expense of this intervention, both in children's lives and in budgetary expenditures. A cost analysis of one large, well‐established community‐based program to treat SAM in Niger found an average cost per child of 149 euros (US$ 175 in today's currency), with cost breakdowns of US$ 83 for outpatient treatment costs and US$ 149 for inpatient treatment costs, respectively (Isanaka et al, ). Indeed, among 10 interventions recommended to improve maternal and child nutrition, SAM management was by far the most expensive, estimated at a total cost of $2.6 billion to achieve 90% coverage in the 34 highest‐burden countries (2010 international dollars; Bhutta et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(International NGO, Somalia) Global-and regional-level respondents confirmed these issues; one said that "UNICEF and WFP kind of have a turf war going on," since WFP has become increasingly involved in managing MAM (bilateral agency, global level). Another global respondent said: with cost breakdowns of US$ 83 for outpatient treatment costs and US$ 149 for inpatient treatment costs, respectively (Isanaka et al, 2017). Indeed, among 10 interventions recommended to improve maternal and child nutrition, SAM management was by far the most expensive, estimated at a total cost of $2.6 billion to achieve 90% coverage in the 34 highest-burden countries (2010 international dollars; Bhutta et al, 2013).…”
Section: Reservations About the Appropriateness Of Rutf As The Singmentioning
confidence: 99%